2004
DOI: 10.1118/1.1813891
|View full text |Cite
|
Sign up to set email alerts
|

CSnrc: Correlated sampling Monte Carlo calculations using EGSnrc

Abstract: CSnrc, a new user-code for the EGSnrc Monte Carlo system is described. This user-code improves the efficiency when calculating ratios of doses from similar geometries. It uses a correlated sampling variance reduction technique. CSnrc is developed from an existing EGSnrc user-code CAVRZnrc and improves upon the correlated sampling algorithm used in an earlier version of the code written for the EGS4 Monte Carlo system. Improvements over the EGS4 version of the algorithm avoid repetition of sections of particle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 20 publications
6
38
0
Order By: Relevance
“…The chamber used for this representative plot is inherently waterproof so this effect is not observed. Buckley et al 29 showed that there is very little difference between their Monte Carlo calculated P cel values and those in TG-51.…”
Section: Iiia Comparison To Other Studiesmentioning
confidence: 94%
“…The chamber used for this representative plot is inherently waterproof so this effect is not observed. Buckley et al 29 showed that there is very little difference between their Monte Carlo calculated P cel values and those in TG-51.…”
Section: Iiia Comparison To Other Studiesmentioning
confidence: 94%
“…In addition to calculating the two dose values in one run, the water/silicon dose ratio D water / D Si is calculated directly by CSnrc. 16 This dose ratio represents the Si diode response in a water phantom if we assume the charge released is directly proportional to the energy deposited as described in Sec. II A.…”
Section: B Calculation Of Water/silicon Dose Ratio and Stopping-powementioning
confidence: 99%
“…In addition, we also study the energy dependence of the response of the diode model, which is an important characteristic of any radiation detector, and the field-size dependence of the response of the diode model, which is important for output factor measurements in clinical practice. The code used in this work is CSnrc, 16 a new EGSnrc user-code that implements a correlated sampling technique. CSnrc is very efficient in calculating dose ratios for similar geometries that are commonly encountered in radiation dosimetry.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Buckley and Rogers [4] calculated P wall for Farmer-type chambers with various wall materials using the EGSnrc/CSnrc-code [5]. The P wall values vary by 0.8% with the wall material.…”
Section: Introductionmentioning
confidence: 99%